Development and validation of the multi-dimensional health resilience scale for community-dwelling adults - Ge, Lixia; Yip, Wan Fen; Li, Ruijie; Chua, Eric Siang Seng; Ho, Moon-Ho R.; Ho, Andy Hau Yan; Chua, Evon Yiwen; Cheng, Dolly; Leong, Ian Yi Onn; Chieh, Pann Pei; Tan, Woan Shin (Frontiers in Public Health, 2025)
IntroductionResilience measures generally are not health specific, nor do they account for the multiple dimensions required for individuals to overcome health challenges. To bridge this gap, we developed and validated a multi-dimensional Health Resilience Scale (HRS) for community-dwelling adults in Singapore.MethodsWe followed standard procedures to develop health resilience construct, identify dimensions, and generate potential items. Expert review and cognitive interviews were conducted to assess content validity and item clarity. The refined 35-item HRS was administered to 650 eligible community-dwelling adults in a cross-sectional survey, along with validation measures, to assess construct validity (including factorial, concurrent, convergent, and divergent validity) and internal consistency reliability.ResultsExploratory factor analysis revealed five factors with 22 items, each factor containing 3 to 5 items. Confirmatory factor analysis confirmed the five-factor structure with good model fit. The five factors identified in the analysis were conceptualised as the following dimensions of the HRS: “Health mindset,” “Perceived health access,” “Social resourcefulness,” “Relational support,” and “Adaptive adjustment.” The dimensions of “Health mindset,” “Perceived health access,” and “Adaptive adjustment” exhibited moderate and positive correlations with psychological resilience (concurrent validity) as well as hope and self-efficacy (convergent validity). All dimensions had weak or no correlation with maladaptive coping, depression, and anxiety measures (divergent validity). Individuals with better health status scored higher, while those with recent health adversity scored lower on the HRS, confirming divergent validity. Internal consistency reliability was confirmed with Cronbach’s alpha exceeding 0.80 for the total scale and ranging from 0.73 to 0.88 for individual dimensions.ConclusionThe 22-item multi-dimensional HRS demonstrated good reliability and validity, making it an effective tool for assessing health resilience and guiding initiatives aimed to enhance well-being among community members.